2008
DOI: 10.1017/s0022215108002569
|View full text |Cite
|
Sign up to set email alerts
|

Otological and vestibular symptoms in patients with low grade (Quebec grades one and two) whiplash injury

Abstract: No patients reported otological or persistent vestibular symptoms in the acute phase following their whiplash injury. This suggests that caution should be exercised when attributing these symptoms to such an injury. Before whiplash injuries are admitted as an aetiological factor in the development of such symptoms, other causes should be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
6
1
1
Order By: Relevance
“…95 There is a remarkable difference between the reported prevalence (range, 10%-15%) of otological symptoms several months after whiplash injury. 97 These data point to a delay in the development of tinnitus after neck trauma. 97 These data point to a delay in the development of tinnitus after neck trauma.…”
Section: Whiplash/neck Traumamentioning
confidence: 97%
“…95 There is a remarkable difference between the reported prevalence (range, 10%-15%) of otological symptoms several months after whiplash injury. 97 These data point to a delay in the development of tinnitus after neck trauma. 97 These data point to a delay in the development of tinnitus after neck trauma.…”
Section: Whiplash/neck Traumamentioning
confidence: 97%
“…63 One study of individuals evaluated for legal claims from whiplash injury reported a very low proportion (3.7%) having any vestibular symptoms or complaints. 64 It may be that the actual physical trauma of a mTBI is a less important factor than is female gender and the presence of preinjury depression and anxiety, posttraumatic stress disorder, and pain, which predispose to prolonged postconcussive syndrome symptoms. [65][66][67] As one hypothesis goes, mild head trauma may be the initiating factor, but it is the pre-existing psychological condition that causes the prolonged postconcussive syndrome symptoms.…”
Section: Prognosismentioning
confidence: 99%
“…Vehicle collisions rear-end shunts have lead to whiplash injuries to the cervical spine that have been associated with unilateral tinnitus developing immediately following the injury (Rowlands et al, 2009).…”
Section: Bannister Fairfi Eld General Hospital Bury Ukmentioning
confidence: 99%